2014
DOI: 10.1111/bph.12418
|View full text |Cite
|
Sign up to set email alerts
|

Midkine in nephrogenesis, hypertension and kidney diseases

Abstract: Midkine (MK; K; gene abbreviation, Mdk: mus musculus, MDK: homo sapiens) is a multifunctional heparin‐binding growth factor that regulates cell growth, survival and migration as well as anti‐apoptotic activity in nephrogenesis and development. Proximal tubular epithelial cells are the main sites of MK expression in the kidneys. The pathophysiological roles of MK are diverse, ranging from the development of acute kidney injury (AKI) to the progression of chronic kidney disease, often accompanied by hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 59 publications
2
25
0
Order By: Relevance
“…However, the mechanisms by which hypertension contributes to the progression of renal injury is not clear. In this study, we observed that AngII exposure resulted in significant up-regulation of TNFα and IL-1β in NRK52E cells after 6 h. Our results are consistent with those of previous studies which have shown that AngII infusion increases the production of PIC in rat kidneys [53][54][55]. Although previous studies have investigated the effects of AngII on kidneys, the upstream signaling mechanism are not well understood.…”
Section: Discussionsupporting
confidence: 91%
“…However, the mechanisms by which hypertension contributes to the progression of renal injury is not clear. In this study, we observed that AngII exposure resulted in significant up-regulation of TNFα and IL-1β in NRK52E cells after 6 h. Our results are consistent with those of previous studies which have shown that AngII infusion increases the production of PIC in rat kidneys [53][54][55]. Although previous studies have investigated the effects of AngII on kidneys, the upstream signaling mechanism are not well understood.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with this concept, the current study revealed no effect of either SPARC, SPARCL1 or MGE8 alone on (pro)renin synthesis by As4.1 cells. Additionally, ligands that are known to be involved in blood pressure regulation (NPPC, or natriuretic peptide precursor C), diabetic nephropathy (LGALS1 or galectin-1) 26 , nephrogenesis (MDK or midkine) 27 , renal fibrosis (WFDC2, or WAP four-disulfide core domain protein 2) 28 , and renal injury prevention (FSTL1, or follistatin-related protein 1) 29 also did not directly affect (pro)renin synthesis by As4.1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…They were first divided into two subgroups. One of these represented early proximal tubule progenitor cells, expressing midkine, which is associated with the early proximal tubule (Sato and Sato, 2014), as well as Osr2, Lhx1 and Jag1, which are markers of early nephron developmental stage cells, preceding the proximal tubule (Fig. S2).…”
Section: Single-cell Gene Expression Atlas Of Newborn Kidney Developmentmentioning
confidence: 99%